2015
DOI: 10.1002/lary.25554
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different neuroprotective agents in facial nerve injury: An experimental study

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We found Res improved motor function at a dose of both 200 and 50 mg/kg, but the higher dose led to better motor repair than the lower dose. Although the doses of Res we used were higher than those used previously to alleviate the peripheral nerve injury-induced motor deficit, we obtained the motor repair within a period of treatment much shorter than before (Bagriyanik et al, 2014 ; Tanyeri et al, 2015 ). For example, in a study performed by Tanyeri et al, it took 2 weeks to observe motor recovery after i.p.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We found Res improved motor function at a dose of both 200 and 50 mg/kg, but the higher dose led to better motor repair than the lower dose. Although the doses of Res we used were higher than those used previously to alleviate the peripheral nerve injury-induced motor deficit, we obtained the motor repair within a period of treatment much shorter than before (Bagriyanik et al, 2014 ; Tanyeri et al, 2015 ). For example, in a study performed by Tanyeri et al, it took 2 weeks to observe motor recovery after i.p.…”
Section: Discussionmentioning
confidence: 83%
“…For example, in a study performed by Tanyeri et al, it took 2 weeks to observe motor recovery after i.p. treatment with 30 mg/kg Res in a rat model of facial nerve crush injury (Tanyeri et al, 2015 ). In another study, Bagriyanik et al found that motor amelioration was identified 2 weeks after i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, one given compound is assayed for one disease or for two/three closely related diseases. In the case of RSV, results from clinical trials have been reported for menopause (Chow et al., ; Evans, Howe, & Wong, ; Yoshino et al., ; Zern et al., ) and for an incredibly high number of ailments: ulcerative colitis (Samsami‐kor, Daryani, Asl, & Hekmatdoost, ), lung affections/infections (Culpitt et al., ; Miraglia Del Giudice et al., ; Varricchio et al., ), allergic rhinitis (Miraglia Del Giudice et al., ), liver diseases (Chachay et al., ; Faghihzadeh, Adibi, & Hekmatdoost, ; Faghihzadeh, Adibi, Rafiei, & Hekmatdoost, ; Heebøll et al., ), chronic kidney disease (Migliori et al., ), benign prostate hyperplasia (Kjaer et al., ), schizophrenia (Zortea et al., ), memory performance/cognition/brain glucose consumption/AD (Cuzzola et al., ; Kennedy et al., ; Turner et al., ; Wightman et al., ; Witte, Kerti, Margulies, & Flöel, ), Friedreich ataxia (Yiu et al., ), facial nerve injury (Tanyeri, Celik, Erbas, Oltulu, & Yilmaz Dilsiz, ), diabetes/metabolic syndrome/insulin resistance (Bhatt, Thomas, & Nanjan, ; Brasnyó et al., ; Chen et al., ; Crandall et al., ; Fujitaka et al., ; Goh et al., ; Méndez‐del Villar, González‐Ortiz, Martínez‐Abundis, Pérez‐Rubio, & Lizárraga‐Valdez, ; Olesen et al., ; Skroza et al., ; Thazhath et al., ; Tomé‐Carneiro et al., ), inflammation (Olesen et al., ), facial redness (Ferzli, Patel, Phrsai, & Brody, ), cancer/metastases (Brown et al., ; Chow et al., ; Howells et al., ; Ji et al., ; Patel et al., ; Popat et al., ), cardiovascular diseases/lipoprotein status/obesity (Agarwal et al., ; Amato et al., ; Bakker et al., ; Biesinger et al., ; Cruz, ; Dash, Xiao, Morgantini, Szeto, & Lewis, ; De Groote et al., …”
Section: Safety and Efficacy Based On Clinical Trial Resultsmentioning
confidence: 99%
“…16,17 In traumatic facial nerve injuries, topical and systemic steroids were both shown to accelerate recovery in rodent models. 18,19 The administration of methylprednisone within 24 hours after traumatic optic neuropathy was also associated with improved visual acuity. 20 Conversely, numerous studies showed corticosteroids to be ineffective in preventing neuronal injury or in hastening recovery among patients undergoing parotidectomy.…”
Section: Discussionmentioning
confidence: 99%